Draft Genome Sequences of Eight Pseudomonas aeruginosa Corneal Infection Isolates - Raghuram, Vishnu (Microbiol Resour Announc, 2020)
Pseudomonas aeruginosa is the major cause of bacterial keratitis, a sight-threatening ocular infection that can occur in contact lens wearers, as well as in others. Here, we report the draft genomes of 8 different P. aeruginosa corneal isolates, adding to the list of publicly available corneal infection-associated P. aeruginosa genomes.